Relationship between gastroesophageal reflux disease and laparoscopic sleeve gastrectomy: a narrative review - Flavius Mocian; Marius Coroș (Videosurgery and Other Miniinvasive Techniques, 2021)
This paper aims to revisit the relationship between gastroesophageal reflux disease and laparoscopic sleeve gastrectomy in obese patients by reviewing the recent available literature, in the form of a narrative review. The interpretation of the current evidence is challenged by the fact that published data are contradictory and comparison between studies is difficult. Most studies investigate the presence of gastroesophageal reflux disease by assessing only the symptoms reported by patients. A few studies have objectively investigated gastroesophageal reflux disease by functional tests and endoscopic evaluation. Also, the surgical technique of laparoscopic sleeve gastrectomy plays an important role in the incidence of postoperative gastroesophageal reflux disease. In conclusion, surgeons must be aware of the existence of gastroesophageal reflux disease and, at the same time, patients should be informed regarding the possible effect of laparoscopic sleeve gastrectomy on gastroesophageal reflux disease.